Analisis Pengaruh Kepemilikan Manajerial terhadap Kebijakan Pendanaan dan Dividen (Jurnal Manajemen dan Organisasi, 2016)
Banking regulations required banks to manage their capital structure well, including those related to  managerial ownership, funding and dividend policies. The primary objective of this research is to analyze the influence of managerial ownership on policies of funding and dividend. By using data of 22 banking companies listed at JSX for the period 2008-2012, we find that managerial ownership is not significantly influence funding policy. On the other hand, it negatively and significantly influences dividend policy. Keywords : banking, dividend policy, funding policy, managerial ownership